SEO Underpricing and Market Condition – Evidence from the Listed Companies in Taiwan - Li, Jian-Fa; Liao, Guan-Ting; A. Li, Katherine (Journal of Ecohumanism, 2025)
The purpose of this study is to investigate the factors that influence the underwriting price of seasoned equity offerings (SEOs) for listed companies in Taiwan. The market method, income method, and capital method are utilized to evaluate firm value. Additionally, we examine whether listed companies align with the market conditions hypothesis when issuing SEOs during the period from January 1, 2009, to December 31, 2019. In this study, we categorize the sample data into four market periods. The empirical results demonstrate that regardless of the business valuation method employed, during bull markets, the results consistently align with market conditions. Consequently, the compliance of listed companies with market conditions when conducting SEOs significantly impacts the underwriting price.